1981
DOI: 10.1063/1.329043
|View full text |Cite
|
Sign up to set email alerts
|

Reactive ion etching induced corrosion of Al and Al-Cu films

Abstract: Articles you may be interested inThe microstructure of submicrometer wide planar-reactive ion etched versus trench-damascene AlCu lines A process for improved Al(Cu) reactive ion etching Summary Abstract: Surface changes induced in Al/Cu/Si and photoresist films by reactive ion etching J. Vac. Sci. Technol. A 4, 749 (1986); 10.1116/1.573801 Summary Abstract: Reactive ion etching induced corrosion of Al and Al-Cu films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…These plasmas are often used in sequence with an 0 2 plasma that removes polymeric material and restores a layer of protective aluminum oxide. A thermal oxidation treatment at 300-350°C and 1-atm 0 2 [104] is yet another technique that was found to be effective in passivating Al. A thermal oxidation treatment at 300-350°C and 1-atm 0 2 [104] is yet another technique that was found to be effective in passivating Al.…”
Section: Postetch Corrosionmentioning
confidence: 99%
“…These plasmas are often used in sequence with an 0 2 plasma that removes polymeric material and restores a layer of protective aluminum oxide. A thermal oxidation treatment at 300-350°C and 1-atm 0 2 [104] is yet another technique that was found to be effective in passivating Al. A thermal oxidation treatment at 300-350°C and 1-atm 0 2 [104] is yet another technique that was found to be effective in passivating Al.…”
Section: Postetch Corrosionmentioning
confidence: 99%
“…1 with an overetch of 50% (which varies with topography as well as with the concentration and the distribution of copper in the film). 16 though this may seem to be a low etch ratio when compared to that for other plasma etching processes, it is typical of results obtained in IC production today and is unlikely to improve appreciably in the immediate future. For chips with high copper content in aluminum and perhaps also high aluminum deposition temperature (-400~ the overetch requirement is usually greater than 50%, possibly greater than 80%.…”
Section: Photoresist Issuesmentioning
confidence: 82%
“…During this process step, an oxide forms on the aluminum surface which helps to prevent corrosion of the aluminum lines. 16 In a conventional barrel reactor, this oxide is 20-30 A in thickness and is spectroscopically similar to native aluminum oxide. 4~ Experience has shown that after plasma etching of aluminum, it may be necessary to carry out a more elaborate stripping procedure than is required after other plasma etching processes.…”
Section: Postetch Treatmentmentioning
confidence: 98%
“…Since the passivating native oxide film normally present on the aluminum surface has been removed during etching, chlorine species are left in contact with aluminum, ultimately causing corrosion. Further, carbon contamination and radiation damage caused by particle bombardment may enhance corrosion susceptibility (85). A water rinse or an oxygen plasma treatment after etching lowers the amount of chlorine left on the etched surfaces, but is not adequate to preclude corrosion.…”
Section: Introduction To Microlithographymentioning
confidence: 99%
“…A water rinse or an oxygen plasma treatment after etching lowers the amount of chlorine left on the etched surfaces, but is not adequate to preclude corrosion. Low temperature thermal oxidations in dry oxygen appear effective in restoring a passivating native aluminum oxide film (85). Another method of preventing post-etch corrosion is to expose the aluminum film to a fluorocarbon plasma (86).…”
Section: Introduction To Microlithographymentioning
confidence: 99%